Fragrance components of Gymnadenia conopsea and Gymnadenia odoratissima collected at several sites in Italy and Germany. Issue 13 (1st July 2022) - D'Auria, Maurizio; Lorenz, Richard; Mecca, Marisabel; Racioppi, Rocco; Romano, Vito Antonio; Viggiani, Licia
Abstract: The SPME-GC-MS analysis of the aroma components of Gymnadenia conopsea subsp. conopsea, subsp. densiflora, var. alpina and Gymnadenia odoratissima var. odoratissima, var. idae were reported. The main components of in total 78 found in G. conopsea subsp. conopsea were elemicin, cis-9-hexadecenal, hexadecanal, isoelemicin and (Z)-11-hexadecen-1-ol acetate; in subsp. densiflora benzyl benzoate, eugenol and trans-isoeugenol; in var. alpina benzyl benzoate, methyleugenol and elemicin. In the scent of G . odoratissima var. odoratissima were found 2-phenylethyl acetate, eugenol and pentadecane, in var. idae mainly C15–C21 alkanes and C16, C18 carbonic acids and some isoprenoid-derivatives. As all tested Gymnadenia -taxa are allogamous, the differences in scent composition may play a role in pollinator attraction. Graphical Abstract: UF0001